Strategi Komunikasi Pemasaran Kedai Hegar Coffee & Liwet Melalui Akun Instagram - Ali Alamsyah Kusumadinata; Aditya Ramadhan; Dendi Maulana; Fajar Wiratama (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Business growth in the Food & Beverage sector presents a great opportunity for entrepreneurs in the culinary space to create new markets. This cafÃ© culinary business is very tempting because of its wide target market from various circles. The emergence of New Media or the Internet today has been considered as a major need in modern companies, it aims to carry out marketing promotion activities. The advancement of technology makes business people take advantage of a form of advertising known as buying and selling "Instagrammable concept" has become a new trend for many people in recent years among young people in various big cities. The purpose of this study is to identify Kedai Hegar's marketing communication strategy to the audience through their Instagram account. This research method uses descriptive qualitative and IMC (Integrated Marketing Communication) theory. The study found that Kedai Hegar's marketing communication strategy uses Instagram social media because it is cheap, easy, and has a large market area. Kedai Hegar takes advantage of these technological developments with marketing communication strategies to promote its products on Instagram. Hegar Coffee & Liwet provides a consistent image by presenting high-quality coffee combined with Liwet rice as well as beautiful natural nuances to create the right choice for the audience as a place for healing. Marketing Communication Strategy was created by Hegar Coffee and Liwet, namely with personal selling that involves baristas and waiters interacting directly with consumers on the spot. Furthermore, with Word of Mouth, Kedai Hegar's marketing has increased so that consumers can recommend it to other consumers. Keywords: Brand Image, Instagram, Communication Strategy, Marketing Communication